SOCIOLINGUISTIC CONSTRUCTION OF ISLAMIC ANTI-USURY SLOGANS IN PADANG, INDONESIA: Language, Identity, and Infrastructural Challenges - Wahyudi, M; Putra, Doni Eka; Pratama, Fachmi Achta; Riady, Yasir (Journal of Contemporary Islam and Muslim Societies, 2025)
This study investigates the sociolinguistic framing of anti-usury (riba) slogans in Padang, a Muslim-majority city in Indonesia where enthusiasm for Islamic finance is rising, though practical implementation remains uneven. Using a qualitative descriptive method, the research draws on field observations across 13 neighborhoods, visual documentation, and interviews with 39 purposively selected participants. Anchored in pragmatic politeness theory, symbolic power, and Peircean semiotics, the analysis reveals that the term sharia often substitutes “anti-usury” as a softer, less confrontational expression of ideological stance. This practice reflects a nuanced sociolinguistic strategy of identity signaling. However, a gap persists between symbolic expressions of belief and the limited availability of sharia-based financial infrastructure.Keywords: Anti-usury Slogans, Anti-usury Discourse, Sharia Semantics, Sociolinguistic Behavior, Padang Islamic Identity